2004
DOI: 10.1080/07315724.2004.10719397
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride Increases Neuronal Damage after Traumatic Brain Injury in Rats

Abstract: Thus, amiloride is ineffective in preventing Mg loss after TBI when administered 30 min after trauma. Moreover, by administering amiloride after the TBI-related Mg decline has already been initiated, it may exacerbate injury by, in part by inhibiting Na(+)/Mg(2+) antiport and preventing entry of Mg back into the cell, and also by inhibiting other Na(+) linked transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A growing body of evidence has identified ASIC1a as a possible therapeutic target for the reduction of calcium influx (Wang et al, 2006). Amiloride, a licensed and clinically safe blocker of ASICs, has been shown to be neuroprotective in rodent models of PD (Arias et al, 2008), Huntington's disease (Wong et al, 2008), multiple sclerosis (Friese et al, 2007), and traumatic brain injury (Turner et al, 2004). It is therefore reasonable to assume that Ami has neuroprotective effects on PC12 cells.…”
Section: Discussionmentioning
confidence: 98%
“…A growing body of evidence has identified ASIC1a as a possible therapeutic target for the reduction of calcium influx (Wang et al, 2006). Amiloride, a licensed and clinically safe blocker of ASICs, has been shown to be neuroprotective in rodent models of PD (Arias et al, 2008), Huntington's disease (Wong et al, 2008), multiple sclerosis (Friese et al, 2007), and traumatic brain injury (Turner et al, 2004). It is therefore reasonable to assume that Ami has neuroprotective effects on PC12 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Brains were rapidly removed and the cerebral cortex and hippocampus regions dissected in total and snap frozen in liquid nitrogen, before being stored at 2808C. Cerebral cortex and hippocampus were chosen for analysis because previous studies from our laboratory (Turner et al, 2004;Donkin et al, 2007) have demonstrated significant neuronal damage in these areas of the brain following TBI.…”
Section: Materials and Methods Tbimentioning
confidence: 99%
“…A modified Barnes maze was utilized to perform spatial learning and reference memory tests described by Barnes (1979) and Turner et al (2004). The maze was 122 cm in diameter made of water resistant white material, had 12 holes with a diameter of 9.5 cm equidistant from each other, and 3 cm away from the perimeter.…”
Section: Barnes Maze Test (Spatial Memory and Reference Learning)mentioning
confidence: 99%